Retention of fish-like odontode overgrowth in Permian tetrapod dentition supports outside-in theory of tooth origins. (27th September 2019) - Haridy, Yara; Gee, Bryan M.; Witzmann, Florian; Bevitt, Joseph J.; Reisz, Robert R.
Abstract : Teeth are often thought of as structures that line the margins of the mouth; however, tooth-like structures called odontodes are commonly found on the dermal bones of many Palaeozoic vertebrates including early jawless fishes. 'Odontode' is a generalized term for all tooth-like dentine structures that have homologous tissues and development. This definition includes true teeth and the odontodes of early 'fishes', which have been recently examined to gain new insights into the still unresolved origin of teeth. Two leading hypotheses are frequently referenced in this debate: the 'outside-in' hypothesis, which posits that dermal odontodes evolutionarily migrate into the oral cavity, and the 'inside-out' hypothesis, which posits that teeth originated in the oropharyngeal cavity and then moved outwards into the oral cavity. Here, we show that, unlike the well-known one-to-one replacement patterns of marginal dentition, the palatal dentition of the early Permian tetrapods, including the dissorophoid amphibian Cacops and the early reptile Captorhinus, is overgrown by a new layer of bone to which the newest teeth are then attached. This same overgrowth pattern has been well documented in dermal and oral odontodes (i.e. teeth) of early fishes . We propose that this pattern represents the primitive condition for vertebrates and may even predate the origin of jaws. Therefore, this pattern crosses the fish–tetrapod transition, and the retention of this ancestral pattern in the palatal dentition of early terrestrial tetrapods provides strong support for the 'outside-in' hypothesis of tooth origins.